PENGARUH BANK RELATIONSHIP TERHADAP PROFITABILITAS PERUSAHAAN DI INDONESIA - FARAH MARGARETHA; OCKY OCKY (Jurnal Bisnis dan Akuntansi, 2007)
The role of bank is nevertheless important for all firms. More to the point of providing required capital, banks also provide services which are vital for firm’s operation. Based on previous researches, relationship with bank could affect firm’s profitability. Hence, the decision for the numbers of bank relationship can be a considerable factor for improving firm’s performance. Using samples containing firms within manufacturing sector, listed at Jakarta Stock Exchange for the period from 1999 till 2004, this paper examines whether bank relation-ship of firms in Indonesia affects firms’ profitability. The result based on the regression analysis point out bank relationship has an insignificant effect on firm’s profitability in Indonesia. Based on the result, also the fact of the occurrence of banking crisis in the sample period, it is suggestible for firms to have more than a single bank relationship. And last but not least the government should encourage a continuous improvement towards banking industry to avoid and anticipate future banking crisis.